Clinical Description and Outcomes of Australian Children With Invasive Group A Streptococcal Disease. Issue 5 (May 2020) - Thielemans, Elise; Oliver, Jane; McMinn, Alissa; Baker, Ciara; Britton, Philip N.; Clark, Julia; Marshall, Helen; Blyth, Christopher C.; Francis, Joshua; Buttery, Jim; Smeesters, Pierre R.; Crawford, Nigel; et al.
Abstract : Background: Invasive group A streptococcal disease is a severe infection with a high case fatality rate, estimated to cause more than 150, 000 deaths per year worldwide. The clinical presentation of this infection is variable, and early diagnosis can be challenging. There are few data on its short- and longer-term outcomes, especially in children. The aim of this study was to assess the clinical presentation, management and short- and longer-term outcomes of invasive group A streptococcal disease in children in Australia. Methods: We undertook a prospective surveillance study of children with laboratory-confirmed invasive group A streptococcus disease admitted to 7 sentinel tertiary and quaternary pediatric hospitals in Australia between July 2016 and June 2018. We collected demographic and clinical data and contacted patients 6 months after discharge to assess longer-term outcomes. Results: We enrolled 181 children, 7 days to 16 years of age. The principal site of invasive infection was blood (126 children, 69.6%), and the most frequent clinical presentation was pneumonia in 46 children (25.4%). Twenty-six children developed streptococcal toxic shock syndrome (14.4%), and 74 had severe disease (40.9%), including 71 admitted to the intensive care unit. Five children died (2.8%). At discharge and 6 months, 29.3% and 15.2% of the children had persisting health problems, respectively. Conclusions: Invasive group A streptococcal infection in Australian children is frequently severe and has a high long-term morbidity burden, highlighting the need for strengthened clinical care pathways, epidemiologic surveillance and prevention strategies. Abstract : Supplemental Digital Content is available in the text.